Pervaporation membrane reactor study for the esterification of acetic acid and isobutanol using polydimethylsiloxane membrane - Korkmaz, Sevinc; Salt, Yavuz; Hasanoglu, Ayca; Ozkan, Semra; Salt, Inci; Dincer, Salih (ELSEVIER, 2009)
In this study, isobutyl acetate, a valuable solvent in cosmetics, aroma and paint industries, is produced by pervaporation-esterification equilibrium reaction in a batch pervaporation membrane reactor (PVMR) using homogeneous (sulphuric acid) and heterogeneous (Dowex 50W-X8) catalysts. The effects of catalyst loading, catalyst type, reaction time, membrane thickness, temperature and initial molar ratio of reactants were investigated. A cross-linked polydimethylsiloxane (PDMS) membrane selective to esters was prepared and used in PVMR. Batch reactions were carried out also in a simple batch reactor (SBR) without pervaporation under the same conditions to compare the conversions for the reactions with and without pervaporation. In conclusion, PVMR experiments showed that the PDMS membrane can be used to remove the isobutyl acetate formed selectively with acceptable conversions and pervaporation fluxes. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Pervaporation membrane reactor; Esterification; Isobutyl acetate; Polydimethylsiloxane; LIQUID-PHASE ESTERIFICATION; SEPARATION; ACETATE; Chemistry; Environmental Sciences & Ecology